A combined experimental and theoretical study of diesel fuel injection timing and gaseous fuel/diesel mass ratio effects on the performance and emissions of natural gas-diesel HDDI engine operating at various loads. (15th August 2017) - Papagiannakis, R.G.; Krishnan, S.R.; Rakopoulos, D.C.; Srinivasan, K.K.; Rakopoulos, C.D.
Highlights: Experiments and two-zone modeling studies in natural gas/diesel HDDI engine. Increasing methane concentration increases ISEC, CO and max pressure. Increasing methane concentration reduces NO and soot. Advancing diesel fuel injection timing reduces ISEC, CO and soot. Advancing diesel fuel injection timing increases max pressure and NO. Abstract: Diesel engines find widespread applications in stationary and transportation systems owing to their high fuel efficiency, high torque output, and great size flexibility. However, they still constitute major polluting sources, especially regarding NO and particulate emissions. Therefore, more conventional diesel engines internationally are pursuing the option of conversion to using natural gas as a supplement fuel for the conventional diesel fuel. Many research studies carried out in the aforementioned research field have shown that the specific engine operating mode, in comparison to the conventional diesel one, suffers from higher specific fuel consumption and CO emission. The diesel fuel injection timing and the proportion of the gaseous fuel influence significantly the combustion mechanism, with this effect becoming more evident at part load conditions. Thus, in order to examine the effect of these two parameters on the performance and exhaust emissions, a combined experimental and theoretical investigation is conducted herein on a single-cylinder research, dual fuel (diesel-natural gas), HDDI compression ignition engine. Specifically, through the experimental investigation the effect of diesel fuel injection timing is examined on the performance and exhaust emissions of the engine operating under part load and constant natural gas/diesel mass ratio conditions. Moreover, following validation of the latter, theoretical results concerning the combined effects of both parameters of diesel fuel injection timing and natural gas/diesel mass ratio on the performance and exhaust emissions characteristics of the engine operating at two different loading conditions are obtained, via the application of an in-house, comprehensive, two-zone phenomenological model. The main objective of this assessment is to record and comparatively evaluate the relative impact of these parameters for part and high engine loading conditions. From the experimental and theoretical findings, it is revealed that for the examined test engine operating under constant natural gas/diesel mass ratio, a restricted increase in the diesel fuel injection timing could be a promising solution for engine efficiency improvement and CO emission mitigation, while simultaneously it seemed to increase NO emissions. For extremely advanced diesel fuel injection timing, a simultaneous variation of natural gas/diesel mass ratio at both engine loading conditions could cause problems to the engine structure because, in those cases, the maximum cylinder pressure becomes considerable and hence possibly harmful to the engine structural integrity. The information derived from the present work is valuable, especially if one wishes to define the optimum combination of examined strategies for improving the behavior of an existing engine running under natural gas/diesel operating mode.